Cover Feature: Gold‐Doping of Double‐Crown Pd Nanoclusters (Chem. Eur. J. 72/2017). Issue 72 (22nd November 2017) - Chen, Jishi; Liu, Liren; Liu, Xu; Liao, Lingwen; Zhuang, Shengli; Zhou, Shiming; Yang, Jinlong; Wu, Zhikun
Abstract : Double‐crown Pd4 (PET)8 and Pd5 (PET)10 were successfully doped with gold through two Au atoms replacing one Pd atom, with the other double‐crown structure essentially unchanged. The as‐obtained Au4 Pd2 (PET)8 is the smallest chiral bimetal nanocluster so far, and it bears chirality originating from not only the helixed Au4 Pd2 S8 framework, but also unanimous R or S configuration of sulfur atoms in the enantiomer. Theoretical calculations provide interpretation for some doping‐induced properties. More information can be found in the Full Paper by S. Zhou, J. Yang, Z. Wu et al. onpage 18187 .